BANKING RISKS IN THE CONTEXT OF THE FINANCIAL CRISIS 2008 - Dr. Hadir H Shubbar (Scholar Express Journals, 2023)
This article examines the major risks facing banks in the current financial crisis and how banks have changed their approach to risk assessment and management. The financial crisis of 2008 and the bankruptcy of the LTCM hedge fund highlighted the seriousness of the "too big to fail" problem in financial markets. The assistance that was provided to the largest banks and insurance companies in the United States in 2008 and in subsequent years demonstrated to the largest banks that, due to their systemic importance, they can count on government support in case of financial problems, which further increased the "risk appetite" of these banks, which is clearly seen in the example of a large position on derivatives, which were occupied by these banks as of the end of 2016. The value of the derivatives position in the two largest banks exceeds the value of assets by 30 times, and in some other American banks by 200 times, which increases the risks and makes it possible to implement the financial crisis in the worst-case scenario. New conditions of functioning of financial markets make it necessary to search for new approaches to understanding systemic risk and its regulation
Keywords: bank risks; financial crisis; assessment; diversification